Maxims in Use: EFL Students, Classroom Discourse, and Communicative Effectiveness in University EFL Settings - Pinandhita, Fitra; Susanto, Dias Andris (Global Synthesis in Education Journal, 2026)
This paper focuses on the realization of conversational maxims in EFL students within the classroom interaction in universities and how the realizations affect the effectiveness of communication in EFL. Based on the Cooperative Principle of Grice, the paper utilized a qualitative discourse-based research design where the natural classroom discourse of an English Education program in one of the Indonesian universities is analyzed. The data were gathered in form of classroom observations, audio recordings, and word-to-word transcripts of the lecturer-student interactions. It analyzed to find out the kinds of maxims, maxims obedience and disobedience, and their practical use in teaching. All the four Gricean maxims in classroom communication were found as illustrated in the findings. The most common maxims were the maxim of quantity, the maxim of relation, the maxim of manner, and the maxim of quality (38, 27, 21, and 14 percent). Cases of maximum adherence explained about 62% of the data with strategic violations 38%. Notably, these transgressions were not accidental; they were practical in nature and intimately linked to such pedagogical tasks like the elaboration of responses, control of the interactational flow, the marking of the uncertainty, and negotiating meaning. In line with the previous studies of pragmatic and classroom discourse, the results reveal that controlled violations, especially those of quantity and manner, tended to increase the effectiveness of the communicative process through clarification and increased involvement in academic discourse. As discussed therein, communicative effectiveness in EFL classrooms should be structured not in terms of strict adherence to conversational conventions but rather context-specific pragmatic selections within the context of the instructional purposes. This paper will add to the body of EFL pragmatics research by establishing a case of maxims realization and communicative effectiveness empirically in the context of higher education. Educationally, the results indicate that students can be better pragmatically aware when explicit focus on conversational maxims is given, and the classroom interaction is better